Influence of domain structure on relaxation phenomena in the PZT ceramic - Brus, B.; Ilczhuk, J.; Zarycka, A.; Czerwiec, M. (Functional Materials, 2007)
The temperature dependences of internal friction in PZT ceramics have been obtained in a wide temperature range from the room temperature to that exceeding the phase transition point from ferroelectric to paraelectric phase. The aim of the study was to describe the influence of domain structure on relaxation phenomena in samples of undoped PZT ceramics and multicomponent ceramics doped with Cd and W–Pb(W₁Cd)O₃–PbZrO₃– PbTiO₃, prepared by the sol-gel method and by solid state reaction, respectively, followed by sintering. Basing on the internal friction measurements, the relaxation phenomena observed in examined ceramics have been described. The relaxation peaks connected with interaction point defects and domain walls and viscoelastic motion of domain walls have been observed in the temperature dependences of internal friction. For all relaxation peaks, the values of activation energy H and pre-exponential factor τ₀ have been calculated.